'Your Hair is the Hair of Men': Gender Discord and Depilatories in the Reception History of the Queen of Sheba - Rees, Susannah (Hebrew studies, 2022)
Out of the crucible of Jewish and Islamic imaginative retellings of the encounter between the Queen of Sheba and Solomon in 1 Kgs 10:1-13 emerged an etiological myth which describes the invention of depilatory creams. Drawing on contemporaneous written sources concerning the body's production of hair, its grooming and depilatory practices, I argue that body and facial hair removal was a gendered norm for women. However, Queens and royal women could use their hair to perform a counter-cultural female masculinity. The decision to remove the Queen of Sheba's body hair in later versions of the story aligns the Queen of Sheba with a gender paradigm which was more comfortable for its medieval interpreters. Through the introduction of a sexual element to the encounter and the subsequent association with cosmetics, later retellings simplify the earlier, complex portrayal of the Queen of Sheba as Solomon's royal equal, and instead reduce her to merely a Strange Woman.